DEFENSE MECHANISM IN THE CHARACTER OF HARDIN SCOTT REFLECTED IN ANNA TODD’S AFTER - Siti Nur Shelah; Linusia Marsih (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This thesis tries to analyze a fiction novel written by an American writer, Anna Todd with the novel titled After. This thesis tells about the background faced by Hardin and also his father until there was an unresolved conflict in the relationship between Hardin and his father and Tessa as Hardin's closest person. Here the author focuses on one of the first characters, namely Hardin, his defense mechanisms, and how he shows them. The method used for this thesis is qualitative description because this thesis aims to explain the defense mechanism of the main character in After novel. The data used is taken from the novel itself. The author uses Sigmund Freud's theory of self-defense mechanisms as the main theory to work on this thesis. The data is analyzed by reading, understanding, and identifying. With this analysis, the writer finds that the first character uses denial, projection, rationalization, isolation, identification of aggressors, and displacement. The first character uses this defense mechanism to shape himself so that anxiety does not occur, therefore the main character forms a self-defense mechanism.